Reassessing the Implementation of the 1962 New York Agreement in West Papua: A Study on Treaty Compliance within the Framework of International Law - Petrus Tekege; Silvony Kakoe (Vifada Assumption Journal of Law, 2025)
Purpose: This study reassesses the implementation of the 1962 New York Agreement in West Papua by examining its compliance with international treaty obligations and the principle of self-determination within the framework of international law. It aims to evaluate whether the Agreement was executed in accordance with its normative commitments and to identify the legal implications arising from its implementation. Research Design and Methodology: This research employs a normative-doctrinal legal approach supported by historical and juridical analysis. Primary legal materials include the 1962 New York Agreement, United Nations General Assembly Resolution 2504 (XXIV) of 1969, and the Vienna Convention on the Law of Treaties (1969). These sources are complemented by scholarly articles, official United Nations reports, and archival records. The study utilizes textual, contextual, and teleological interpretations to assess treaty performance, the principle of good faith, and compliance with international legal standards. Findings and Discussion: The findings reveal a significant gap between the normative commitments of the New York Agreement and its practical implementation. Although the Agreement formally guaranteed the right to self-determination, the 1969 Act of Free Choice did not fully conform to internationally accepted standards, particularly regarding popular participation, procedural legitimacy, and genuine expression of political will. The consultative voting mechanism, limited involvement of indigenous Papuans, and Cold War geopolitical pressures influenced the process. Furthermore, United Nations General Assembly Resolution 2504 (XXIV) merely acknowledged the outcome without explicitly endorsing its conformity with democratic self-determination, thereby raising enduring questions concerning treaty compliance and legal legitimacy. Implications: This study contributes to international legal scholarship by offering a doctrinal reassessment of treaty compliance and self-determination in decolonization processes. It underscores the importance of good faith, transparency, and adherence to international legal norms, while providing theoretical insights and practical recommendations for strengthening the legitimacy, accountability, and interpretative integrity of international agreements.